Feedback law with probabilistic certification for Propofol‐based control of BIS during anesthesia. (11th October 2018) - Alamir, Mazen; Fiacchini, Mirko; Queinnec, Isabelle; Tarbouriech, Sophie; Mazerolles, Michel
Summary: This paper proposes a new control strategy for Propofol injection during anesthesia in patients undergoing surgery and where the Bispectral Index (BIS) is considered to be the regulated variable. The proposed control shows the nice feature of being completely independent of the knowledge of the pharmacokinetics that govern the diffusion of the drug. This paper also proposes a certification framework that gives a probabilistic guarantee regarding the containment of the BIS inside the desired interval as well as for the time needed for the BIS to be steered to this interval. Moreover, this certification is given for realistic (and hence very high) level of uncertainties on the parameters that define the unknown‐to‐the‐controller dynamics. This last feature is checked using a widely employed model.